Penerapan Model Pembelajaran Auditory, Intellectually, Repetition (AIR) dengan Pendekatan Lesson Study terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik - Agustiana, Elma; Putra, Fredi Ganda; Farida, Farida (Universitas Islam Negeri Raden Intan Lampung, 2018)
The purpose of this study is to determine whether there is a difference in the average implementation of learning model, intellectual, repetition (AIR) with lesson study approach to the problem solving ability of mathematical learners. This research is a quantitative research type of quasi experiment. Data analysis technique using normality test with Liliefors test and homogeneity test with Barlett test. Hypothesis test using one-way ANOVA test with unequal cells. The result of this research is there is influence of learning model of Auditory, intellectually, Repetition (AIR) with lesson study approach to math problem solving ability. Based on the results of further test using scheffe test, the result shows that AIR learning model with lesson study approach gives better result than AIR and conventional learning model, and AIR learning model is better than conventional learning model.